If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3B + -6 = 2B + 7 Reorder the terms: -6 + 3B = 2B + 7 Reorder the terms: -6 + 3B = 7 + 2B Solving -6 + 3B = 7 + 2B Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-2B' to each side of the equation. -6 + 3B + -2B = 7 + 2B + -2B Combine like terms: 3B + -2B = 1B -6 + 1B = 7 + 2B + -2B Combine like terms: 2B + -2B = 0 -6 + 1B = 7 + 0 -6 + 1B = 7 Add '6' to each side of the equation. -6 + 6 + 1B = 7 + 6 Combine like terms: -6 + 6 = 0 0 + 1B = 7 + 6 1B = 7 + 6 Combine like terms: 7 + 6 = 13 1B = 13 Divide each side by '1'. B = 13 Simplifying B = 13
| -2x+6i=-24yi-14 | | p(15p+4)=3 | | -17+-13= | | 3(x+1)=2 | | 3x^2-11xy+6y^2=0 | | -4x+-x= | | x-35-12y=y^2 | | 0=14x-11x+2 | | -15y+5y= | | X+29=2(x+19) | | x(96+2)=x(80-3) | | 5(y+2)=26 | | 7(96+2c)=7(80-3c) | | x^4+5z^2-14ix^2-24-10i=0 | | 7(96+2)=7(80-3) | | -12+(-63)= | | x-3=3X-13 | | -6-3=7 | | 4y^2-16y+7=0 | | (1[7+y]1)(1[3y-2]1)=0 | | 5x-10=-8 | | 39+42[2+x]=36 | | 11x^2+6x+5=0 | | 2x+-7y=-6 | | 5c-10=-8 | | 3,050,890,000.00-15,000,000.00x=5,550,000.00x+2,085,000,000.00 | | a^2-15ab+54b^2= | | 12x^2-40x-34=0 | | x+4=16-2 | | 6y-2=57-2 | | 5g+.6=-3g-44 | | 8+9[12+x]=23 |